Dessein, dessin, design… Les tribulations d’Idea en régime de haut modernisme américain - Dubreuil, Nicole (RACAR : Revue d'art canadienne / Canadian Art Review, 2012)
This article examines the survival, in post-World War II American abstract painting and especially in the formalist critique interpreting and legitimizing it, of age-old debates concerning the primacy of thought over the mimetic representation of the world that have characterized occidental art theory since Plato. The history of these debates, which the Renaissance took up again and channeled in more aesthetic than metaphysical directions, has been masterfully summarized by Erwin Panofsky in his celebrated essay of 1924 dedicated to idea. One of the pivotal points of that theory as a whole is the relationship established between the plan or intention of the work (dessein) and the drawing or sketch (dessin) which gives it form. This article argues that modernist painting, although radically abstract and apparently devoted to the triumph of the colour field alone, paradoxically fails to reflect upon itself without recourse to a principle of internal articulation wherein subsist avatars of the old alliance between dessein and dessin. The radical transformation of art’s context of production and reception, brought about by the instauration of modernity, introduces however a third term into the equation, design (de-sign), which expresses the fear of a definitive loss: that of the capacity of art to reflect upon the world and provide meaning.